Investigating Nursing Students’ Levels of Knowledge about Alzheimer’s Disease - Kondakci, Dilek Doruk; Mandiracioğlu, Aliye (Makara Journal of Health Research, 2024)
Background: Given that Alzheimer’s disease (AD) has become a major public health problem, this study aimed to investigate the AD knowledge level of nursing students who are health professional candidates. Methods: The population of this cross-sectional study consisted of 346 nursing students taking up a 4-year program. They were asked to fill out a sociodemographic information form and answer questions from the Alzheimer’s Disease Knowledge Scale (ADKS). Results: Among the participants, 67.6% were female and 98.8% were single. The mean age of the students was 20.55 ± 2.05 years. Their general knowledge about AD was low, with a mean ADKS score of 17.6 ± 2.85. The scores of the 4th year students (p = 0.035) and those who received education about the disease beforehand (p = 0.015) were statistically significantly higher than those of the other participants (p < 0.05). No significant relationship with ADKS score was observed for the factors of gender, whether they had elderly relatives, and whether they visited nursing homes. Conclusions: The participating students had a low level of knowledge about AD. Increasing disease-specific education and practices for nursing students and including discussions on AD in compulsory courses is necessary to fill in the knowledge gaps.